Sharia Supervisory Board Characteristics and Anti-Corruption Disclosure: Study of Islamic Banks in Indonesia and Malaysia - Ameraldo, Fedi; Yuliani, Asri; Rizki, Marsi Fella; Rabaya, Abdullah Jihad (AL-MUZARA'AH, 2025)
Corruption continues to pose a substantial challenge for corporations globally, including financial institutions that comply with sharia principles. Islamic banks must prioritize transparency and accountability, as these elements are essential for maintaining ethical governance and revealing their anti-corruption efforts. Despite the growing focus on Anti-Corruption Disclosure (ACD), corruption cases within Islamic banks continue to occur, highlighting concerns regarding the efficacy of Islamic governance mechanisms. This research analyzes the influence of Sharia Supervisory Board (SSB) attributes—namely, number, cross-membership, expertise level, educational qualifications, reputation, and rotation—on ACD. This research employs a quantitative approach, utilizing panel data regression to analyze Islamic banks in Indonesia and Malaysia during the period 2020–2021. The sample, chosen via purposive sampling, includes 16 Islamic banks from a total population of 37, according to established criteria. According to the results, ACD is considerably affected by the number of SSB members, but it is not significantly affected by cross-membership, expertise, educational background, reputation, or rotation. The results provide light on how SSB traits affect ACD improvement and add to the broader conversation on Islamic governance and company transparency.